Perceptions of medical students at Imam Mohammad Ibn Saud Islamic University on histology’s role in clinical course preparation: A cross-sectional study - Eman Ali Elkordy; Mohammed Sulaiman Alwohaibi; Yazeed Musa AlHarbi; Abdulrahman Mohammed Alanazi; Hessah Abdulrahman Almojel; Bandar Nawaf Altimyat; Mohammad Ibrahim Jumaa; Safaa Masoud Hanafy (PLoS ONE, 2025)
Background Histology is a foundational discipline in medical education that connects basic biomedical sciences with clinical practice. However, its perceived relevance may diminish as students progress academically, especially when integration with clinical teaching is limited. This study aimed to assess medical students’ perceptions of histology’s value, teaching quality, and clinical integration at Imam Mohammad Ibn Saud Islamic University across different academic levels. Methods A cross-sectional survey was conducted in January 2025 among 235 undergraduate medical students. A validated, self-administered questionnaire measured students’ perceptions of histology’s importance, teaching effectiveness, clinical relevance, curricular integration, and overall satisfaction. Quantitative data were analyzed using descriptive statistics, ANOVA, logistic regression, and Pearson correlation. Results Most students rated histology as important or very important (73.6%) and acknowledged its contribution to understanding disease mechanisms (88.5%). Satisfaction was strongly associated with perceived applicability, visualization, and integration. Lectures and laboratory sessions were rated as effective or very effective by 75.7% and 76.2% of students, respectively. Additionally, 80.9% supported stronger clinical integration, and 83% preferred the inclusion of clinical examples. Perceptions varied across academic stages, with preclinical students expressing more favorable views. Regression analysis identified teaching quality and integration with clinical content as significant predictors of positive perceptions. Conclusions Histology continues to be a valued component of medical education when delivered through effective teaching and clinically relevant integration. Strengthening instructional design and embedding clinical context throughout the curriculum may enhance student engagement, improve learning outcomes, and sustain the relevance of histology across all stages of medical training.